Mosaic-Like Sequences Containing Transposon, Phage, and Plasmid Elements among Listeria monocytogenes Plasmids - Canchaya, Carlos (American Society for Microbiology (ASM), 2010)
Sequencing of plasmid pLM33 from the food isolate Listeria monocytogenes Lm1 revealed a molecule of 32,307 bp with a G+C content of 36.2%. The plasmid displays a mosaic pattern of identities common to several closely related L. monocytogenes plasmids isolated from food and clinical sources.